2023
DOI: 10.3390/ijms242216307
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Connective Tissue Growth Factor as a Therapeutic Target and Assessing Kahweol as a Potential Drug Candidate in Triple-Negative Breast Cancer Treatment

Jeong Hee Lee,
Jongsu Kim,
Hong Sook Kim
et al.

Abstract: Triple-negative breast cancer (TNBC) is characterized by aggressive behavior and limited treatment options, necessitating the identification of novel therapeutic targets. In this study, we investigated the clinical significance of connective tissue growth factor (CTGF) as a prognostic marker and explored the potential therapeutic effects of kahweol, a coffee diterpene molecule, in TNBC treatment. Initially, through a survival analysis on breast cancer patients from The Cancer Genome Atlas (TCGA) database, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Connective Tissue Growth Factor (CTGF) as Prognostic Marker in Triple-Negative Breast Cancer (TNBC): Research by Lee et al identified CTGF as a significant prognostic marker for TNBC [ 3 ]. As a key component of the extracellular matrix, CTGF is involved in critical cellular functions such as adhesion, migration, proliferation, angiogenesis, and tissue repair.…”
Section: The Latest Research Highlightsmentioning
confidence: 99%
“…Connective Tissue Growth Factor (CTGF) as Prognostic Marker in Triple-Negative Breast Cancer (TNBC): Research by Lee et al identified CTGF as a significant prognostic marker for TNBC [ 3 ]. As a key component of the extracellular matrix, CTGF is involved in critical cellular functions such as adhesion, migration, proliferation, angiogenesis, and tissue repair.…”
Section: The Latest Research Highlightsmentioning
confidence: 99%